ANALISIS PROSPEKTIF STRATEGI PENGEMBANGAN DAYA SAING PERUSAHAAN DAERAH PERKEBUNAN - Yuli Wibowo (AGROINTEK, 2010)
This paper describes application the prospective analysis to formulate the development strategy of competitiveness on the agricultural corporation owned by local government (ACLG). This strategy is developed based on possible scenarios in the future considering key factors of competitiveness and key performance as an entry points of competitiveness. Based on prospective analysis result, the selected scenario for developing ACLG is the optimistic scenario to be a professional corporation. This scenario will take place if all key factors of competitiveness including government policy, human resources ability, financial capital,operational and productive management ability, and financial management ability, develop positively. Meanwhile, operational recommendation of the selected scenario is the local government need decide a conducive policy to develop ACLG becomes a professional corporation. Additionally, the local government need operationally monitor and evaluate the key performance of ACLG that can improve its competitiveness.